PENGARUH DEBT TO ASSET RATIO (DAR) DAN RETURN ON EQUITY (ROE) TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING: Studi Kasus pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang Terdapat di Bursa Efek Indonesia Tahun 2017-2021 (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2024)
This study aims to analyze the effect of Debt to Asset Ratio (DAR) and Return On Equity (ROE) on Stock Returns with Dividend Policy as an intervening variable. This study uses secondary data from the financial statements of manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for 2017-2021. The sampling process used a purposive sampling method with a total of 12 companies in 5 years, so the total research sample was 60 samples. This study uses multiple regression analysis and path analysis using SPSS 24. The results of this study indicate that the Debt to Asset Ratio (DAR) has no significant positive effect on Stock Returns, but Return On Equity (ROE) has a significant positive effect on Stock Returns. Debt to Asset Ratio (DAR), Return On Equity (ROE), and Dividend Policy have no significant positive effect on Stock Returns. However, the Dividend Policy can mediate the Debt to Asset Ratio (DAR) and Return On Equity (ROE) to Stock Returns.
Keywords: Debt to Asset Ratio (DAR); Return On Equity (ROE); Stock Return; Dividend Policy.